Analysis of 5-year Mortality following Lower Extremity Amputation due to Vascular Disease. Issue 1 (11th January 2023) - Beeson, Summer A.; Neubauer, Daniel; Calvo, Richard; Sise, Michael; Martin, Matthew; Kauvar, David S.; Reid, Chris M.
Abstract : Background: Mortality rates following major lower extremity amputations (LEAs) 30 days–365 days postoperative have decreased, but 5-year rates remain high at 40.4%–70%. These data may not reflect recent advances in peripheral arterial disease (PAD) care, and comorbidities of chronic PAD may lead to mortality more frequently than the amputation itself. Mortality rates between diabetic and nondiabetic patients were also analyzed. Methods: The California Office of Statewide Health Planning and Development hospital database was queried for patients admitted January 1, 2007–December 31, 2018. ICD-9-CM codes identified patients with vascular disease and an amputation procedure. Results: There were 26, 669 patients. The 30-day, 90-day, 1-year, and 5-year major LEA mortality rates were 4.82%, 8.62%, 12.47%, and 18.11%, respectively. Weighted averages of 30-day, 90-day, 1-year, and 5-year major LEA mortality rates in the literature are 13%, 15.40%, 47.93%, and 60.60%, respectively. Mortality risk associated with vascular disease after amputation (hazard ratio = 22.07) was 11 times greater than risk associated with amputation-specific complications from impaired mobility (hazard ratio = 1.90; P < 0.01). Having diabetes was associated with lower mortality at 30 days, 90 days, and 1 year ( P < 0.01) but not at 5 years ( P = 0.22). Conclusions: This study suggests that people may be living longer after their major LEA than was previously thought. This study suggests that patients' PAD may play a bigger role in contributing to their mortality than complications from loss of mobility postamputation. Although having diabetes was associated with lower postamputation mortality, the difference was no longer significant by 5 years.